Globalization and Its Effect on Democracy - Ida Farida (UBL, 2013)
The process of globalization is a one-way order and one face. But it is an ambivalent order to the ambiguous direction, the kindness and friendliness of globalization with the ugliness and evil of globalization. In this ambiguity understanding, the effects of globalization on the democracy journey will also depend on what angle we look. Two different angles will result to the different view of democratization. The two angles are not necessarily to be opposed to, moreover seen as the right versus wrong. Both are realities, which means we must understand and see with the wisely view angle. Because the globalization debates on democracy, whether it is good or bad is the same length as the history of the human existence on the earth.